Det digitale imperativ: En epistemologisk bestræbelse [The Digital Imperative: An Epistemological Endeavour] - Jensen, Sisse Siggaard (MedieKultur: Journal of media and communication research, 2014)
In this article, it is argued that third wave digital humanities research is essential for our understanding of how the data streams of status-updates, self-profiling, micro-coordination, micro-blogging, and vlogging as produced by the digital infrastructures of social networking sites increasingly impact human relations and the ‘structure of feeling’ (Berry, 2012). Four emergent themes are analysed based on Facebook data produced by 73 young participants (ages 20-24) in a digital humanities university course (2013). The themes are: Facebook Friends, Events, Self-Profiling and Stalking. Two concept pairs guide the analyses: ‘connectedness and connectivity’ (van Dijck, 2013) and ‘visibility and surveillance’ (Bucher, 2012). Tensions are identified between interpersonal norms and the impact of Facebook data streams relative to friendship, credibility, accountability, prestige, self-promotion, and mutual interest. It is concluded that the epistemological endeavour as summarized by the title ‘the digital imperative’ is to produce knowledge that will help us advance individual as well as collective awareness of the complex and intricate interrelations of data streams and human relations.